Aspiracje Ukrainy wobec Unii Europejskiej - Hurska-Kowalczyk, Liana (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The evolution of the ambitions of the Ukrainian authorities regarding integration with the EU is discussed in the paper. The current attitudes of political parties represented in Parliament towards the European Union, as well as the attitude of Ukrainian society towards the integration of the country with the EU is analyzed. Attention is focused on the Eastern Partnership as the EU’s response to the aspirations of the Ukrainian political elites toward integration with the EU. The process of working out a new agreement between Ukraine and the EU, that is to replace the Partnership and Cooperation Agreement, is analyzed. In the conclusions the principal barriers to the integration of Ukraine with the EU are highlighted.
Ukrainian aspirations concerning the European Union